1997
DOI: 10.1037/h0080213
|View full text |Cite
|
Sign up to set email alerts
|

Distress and coping among women with HIV infection: Preliminary findings from a multiethnic sample.

Abstract: In a multiethnic sample of 53 women with HIV/AIDS, nearly 40% reported clinically significant levels of depression symptomatology and anxiety. Compared to a nonpatient norm, distress levels were higher among the Latina, African-American, and white women who made up the HIV sample. Prayer and rediscovery of self were their most frequent coping responses, suggesting that clinicians working with HIV/AIDS populations not overlook the importance of spiritual faith and practices in adapting to HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
40
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(44 citation statements)
references
References 49 publications
4
40
0
Order By: Relevance
“…Although high rates of depressive symptoms have been reported in other populations of women with HIV disease (Bennetts et al, 1999;Cook et al, 2002;Hudson et al, 2001;Kaplan et al, 1997;Miles et al, 1997;Moneyham et al, 2000;Morrison et al, 2002;Moore et al, 1999), the results suggest that the prevalence of depression among rural women with HIV disease may be much higher than for other populations of HIV positive women. Because the rate of high levels of depressive symptoms reported in the study population are much higher even than that reported among rural women in general (as high as 40%) (Berry, 1993; Hoyt et al, 1997; Marx et al, 2001), it appears that the onset of a chronic illness such as HIV disease has a devastating effect on women already vulnerable to depressive symptoms because of the characteristics of the rural environments in which they live.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Although high rates of depressive symptoms have been reported in other populations of women with HIV disease (Bennetts et al, 1999;Cook et al, 2002;Hudson et al, 2001;Kaplan et al, 1997;Miles et al, 1997;Moneyham et al, 2000;Morrison et al, 2002;Moore et al, 1999), the results suggest that the prevalence of depression among rural women with HIV disease may be much higher than for other populations of HIV positive women. Because the rate of high levels of depressive symptoms reported in the study population are much higher even than that reported among rural women in general (as high as 40%) (Berry, 1993; Hoyt et al, 1997; Marx et al, 2001), it appears that the onset of a chronic illness such as HIV disease has a devastating effect on women already vulnerable to depressive symptoms because of the characteristics of the rural environments in which they live.…”
Section: Discussionmentioning
confidence: 69%
“…Recent investigations of HIV-positive women (Bennetts et al, 1999;Cook et al, 2002;Hudson et al, 2001;Kaplan, Marks, & Mertens, 1997;Miles, Burchinal, Holditch-Davis, Wasilewski, & Christian, 1997;Moneyham, Sowell, Seals, & Demi, 2000;Moore et al, 1999;Morrison et al, 2002) report high rates of depressive symptoms. In the limited number of studies of depression in HIV/AIDS populations that included females, women consistently reported significantly higher levels of depressive symptoms than their male counterparts (Bennetts;Berry, 1993;McCain & Cella, 1995).…”
mentioning
confidence: 99%
“…That study sample was also composed mostly of HIV-positive married women, with a mean age of 36.1 years old and low levels of education, differing from our sample only in the item employment status, since most of women evaluated by those authors were unemployed. 6 However, there have been other studies that evaluated samples of HIV-positive women with quite different sociodemographic characteristics, such as lower mean age 17 and predominantly single. 18 The variability of the results is likely related to the differences between the study samples and between the periods in which the studies were carried out.…”
Section: Discussionmentioning
confidence: 99%
“…Feelings of isolation and loneliness may emerge in the wake of these events (Landau, 1980;Tillich, 1980). While several studies concerning loneliness in the HIV-infected population exist, they have either focused on gay/bisexual men, or employed small samples of women (Kaplan, Marks, & Mertens, 1997;Pace & Stables, 1997;Straits-Troster et al, 1994). In relation to existential loneliness in particular, only Cherry and Smith (1993) to our knowledge discuss its presence in their sample of HIV infected gay males.…”
mentioning
confidence: 99%